Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1136/bmjopen-2021-053622
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Doppler screening for fetuses at risk of adverse outcomes: a multicountry cohort study of the prevalence of abnormal resistance index in low-risk pregnant women

Abstract: Introduction Few interventions exist to address the high burden of stillbirths in apparently healthy pregnant women in low- and middle-income countries (LMICs). To establish whether a trial on the impact of routine Doppler screening in a low-risk obstetric population is warranted, we determined the prevalence of abnormal fetal umbilical artery resistance indices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…A recent multi-country study (Ghana, India, Kenya, Rwanda, and South Africa) found routine Doppler screening in a low-risk obstetric population an effective tool for reducing stillbirth rates. 26 In France, antenatal detection of fetal growth restriction (FGR ) was found to be protective against stillbirth, but despite detection of FGR, over 40% of stillbirths occurred among SGA babies. 27 There is a major focus on small size at birth, however increasing evidence indicates that large for gestational age, which may be associated with the maternal metabolic environment, is also associated with an increased risk of stillbirth.…”
Section: Discussionmentioning
confidence: 99%
“…A recent multi-country study (Ghana, India, Kenya, Rwanda, and South Africa) found routine Doppler screening in a low-risk obstetric population an effective tool for reducing stillbirth rates. 26 In France, antenatal detection of fetal growth restriction (FGR ) was found to be protective against stillbirth, but despite detection of FGR, over 40% of stillbirths occurred among SGA babies. 27 There is a major focus on small size at birth, however increasing evidence indicates that large for gestational age, which may be associated with the maternal metabolic environment, is also associated with an increased risk of stillbirth.…”
Section: Discussionmentioning
confidence: 99%
“…-Delphi Consensus Statement for FGR* includes absent end-diastolic flow (in isolation) and umbilical/uterine artery PI > 95th percentile, CPR < 5th percentile (in combination with other indicators) (43) -Umbiflow™: RI ≥ 75th percentile (Pattinson graphs) (48,100) Placental grading: appearance on ultrasound…”
Section: Antenatal Period: Foetal Growth Assessmentmentioning
confidence: 99%
“…The Umbiflow International study, sponsored by the World Health Organization, conducted in 5 LMICs (Ghana, India, Kenya, Rwanda, and South Africa) reported an overall prevalence of 6.9% of abnormal UmA-RI among LRMs, with the highest prevalence recorded in Ghana. 30 A low-risk pregnancy was defined in all these studies as a pregnant woman attending nonspecialist antenatal care clinics and classified as "low risk" at the time of recruitment according to local clinical guidelines, based on their obstetric and clinical assessment. For South Africa, this is guided by the basic antenatal care plus (called "BANC-Plus") program, following the World Health Organization's recommendations for a positive pregnancy experience.…”
Section: Practical Use Of the Screening Systemmentioning
confidence: 99%
“… The Umbiflow International study, sponsored by the World Health Organization, conducted in 5 LMICs (Ghana, India, Kenya, Rwanda, and South Africa) reported an overall prevalence of 6.9% of abnormal UmA-RI among LRMs, with the highest prevalence recorded in Ghana. 30 …”
Section: Practical Use Of the Screening Systemmentioning
confidence: 99%
See 1 more Smart Citation